Rastros e memórias : etnografia dos vaqueiros do sertão (Floresta – PE) - Pereira, Renan Martins (2017)
This dissertation is about the vaqueiros (cowboys) of the municipality of Floresta, sertão of Pernambuco (hinterland), Brazilian northeast, where I conducted my fieldwork from February to May 2016. It is an ethnography about the disputed position of being a vaqueiro, since perspectives that, far from considering it an historical resistance, covered by regionalism and traditionalism, demonstrate the ways in which, nowadays, many vaqueiros are vaqueiros without being true. It means to say that not everyone is in fact vaqueiros, vaqueiros mesmo, in other words, the real ones. In the face of these contradictions and evaluations, I divided the ethnography into three chapters. In the first, I bring a methodological discussion about how my friends characterized what should be, according to them, my analytical object par excellence. In this case, the real cowboy, original and authentic. Afterward, I will discuss some local strategies whose proposal is to turn the category vaqueiro in something essential. Then, I will see how it simultaneously multiply the same category in unexpected ways, in ways that couldn’t one day be imagined. For this reason, the second chapter analyzes how some interlocutors specifically innovate their relationships with the herd, the drought and the past. In the third and last, memory became the central theme of the discussion. According to my arguments, being a vaqueiro gains new senses in the present, taking into account the knowledge of wise storytellers, whose memories glorify them as more cowboys than others, because they lived in old times, the revered past. At the end of the same chapter, it is the human-animal relationships that gain prominence, in the context of the pegas de boi no mato or vaquejada. My contribution is that, in addition to being disputed and prestigious, being a vaqueiro is also an inventive and procedural position. In this sense, the category in question gains a plastic nature in my ethnographic analysis, whose proposal is to understand that there isn’t only the prospect of the end – that the vaqueiros are disappearing or being transformed into something other than the masters of ancient times – but also the actual perspectives of some cowboys who, in turn, do not consider themselves deserters of what they conventionally call tradition, understood as the resource of memory in which are drawn the traits that equate, and at the same time, differentiate all of them from whom is more true, given the uncertainties of being a vaqueiro in the future.